2017
DOI: 10.1007/s00393-017-0405-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasonographic enthesopathy in inflammatory rheumatic diseases

Abstract: Compared to RA, US and clinical examination of enthesitis in patients with axial SpA should focus on the calcaneal enthesitis region. In axial SpA, ultrasonographic enthesitis is associated with impaired quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In another study from our country, BASDAI and total physical examination scores of enthesitis and MASEI scores were positively correlated in SpA patients . Also, we found significant moderate correlation between MASES scores and PD scores but not GS scores in patients with AS in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…In another study from our country, BASDAI and total physical examination scores of enthesitis and MASEI scores were positively correlated in SpA patients . Also, we found significant moderate correlation between MASES scores and PD scores but not GS scores in patients with AS in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…Most of the previous studies have failed to show any correlation between US and BASDAI,[ 12 , 17 , 36 , 38 , 39 , 41 , 42 ] besides a few studies. [ 18 , 19 , 40 ] Although these studies may suggest that US may be insufficient for disease activity evaluation, some authors have also argued that the current disease activity scales may be inadequate in expressing the real disease state. [ 43 , 44 ] BASDAI is a subjective measure of symptoms and is based on patients’ responses on a self-administered questionnaire; hence, the score may be affected by other concurrent pain-causing illnesses, such as chronic pain and fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%
“…Hamdi et al[ 16 ] found that Doppler scores were correlated with ASQoL. Suleyman et al[ 19 ] found a moderately significant correlation between ASQoL and MASEI. Nonetheless, further studies are needed to provide adequate information on this subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Regardless of the age of report or the modalities used, conflicting data have been reported until very recently. [3][4][5] Although it has been suggested that enthesitis in RA may be secondary to articular synovial inflammation or based on the involvement of synovial membrane lining the tendon sheaths and the bursae, no direct evidence has yet been reported. 6 In this study, we aimed to find a clue to the fundamental inflammatory process underlying AT enthesis in patients with RA by analyzing the association between the presence of RC bursitis or AT enthesitis and clinical data.…”
Section: Introductionmentioning
confidence: 99%